Determination of Lansoprazole and Simvastatin via area under curve and ion pair methods - Ayman Sadiq Alsamarraie; Khalaf F. Alsamarrai (Tikrit Journal of Pure Science)
A two simple, sensitive, and economic methods were developed for the determination of lansoprazole and simvastatin in their pure and pharmaceutical dosages forms . first method based on measurement of area under curve (AUC) for zero order spectrum and the second method based on formation of ion pair complex between each of both drugs and Bromo phenol blue dye. Beer's law obeyed in concentrations ranges of (4-70 μg.ml-1) and (4-50 μg.ml-1) in the first method and (1-70 μg.ml-1) and (1-60 μg.ml-1) in the second method for lansoprazole (LNZ) and simvastatin (SMV) respectively . Average recovery percentage were (99.43%) and (99.36%) in the first method , and (99.71%) and (100.18%) in the second method for LNZ and SMV respectively. The RSD% values were (0.0044-0.0172%) and (0.1041-0.4129%) for LNZ in first and second methods, and (0.0097-0.0311%) and (0.1358-0.5165%) for SMV in the two methods mentioned above. Limit of detection of LNZ in the first method were (0.185×10-3 μg.ml-1)  and (0.268×10-3 μg.ml-1)  in the second method . While limit of quantification were (0.227×10-3 μg.ml-1) and (0.204×10-3 μg.ml-1) in the first method and (0.894×10-3 μg.ml-1) and (0.68×10-3 μg.ml-1) in the second method for LNZ and SMV respectively. The two methods were successfully applied for the determination of both drugs in pure and pharmaceutical dosages forms .